Coherent Control of Nuclei and X-Rays - Liao, Wen-Te (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
Novel coherent light sources such as x-ray free-electron lasers open exciting prospects for the interaction of light with nuclei. The thesis "Coherent Control of Nuclei and X-rays" covers this still-developing field and proposes, in a daring attempt to revolutionize nuclear physics, three innovative schemes for taming nuclei using coherent effects. The theoretical explorations, which address control of nuclear quantum states, a nuclear memory for single photons in future photonic circuits, and optimized concepts for a nuclear clock, make use of new approaches at the borderline between nuclear physics and quantum dynamics. The result is a well written work, impressive in its stimulating style and promising ideas.